2017
DOI: 10.1016/j.micron.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

V-shaped pits in HVPE-grown GaN associated with columnar inversion domains originating from foreign particles of α-Si3N4 and graphitic carbon

Abstract: The v-shaped pits (so-called V-pits) observed in hydride-vapor-phase-epitaxy-grown GaN and associated with the columnar inversion domains originating from foreign particles were investigated. The inversion domains on the front and back surfaces of the test sample were recognized after chemical mechanical polishing. It was found that the V-pits originate from the columnar inversion domains. The inversion domains, in turn, arise from the particles that exist on a low-temperature GaN buffer layer on sapphire subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Secondly, the uncertainty in each of these L-APT and TEM EDS composition measurements has not been quantified. Finally, there are many different factors besides contamination that can influence inversion domain formation [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the uncertainty in each of these L-APT and TEM EDS composition measurements has not been quantified. Finally, there are many different factors besides contamination that can influence inversion domain formation [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10] One evident issue in performing GaN growth along the c-direction is the generation of Vshaped pits [11][12][13][14] on its surface, which might be caused by dust particles, irregularly generated polycrystalline and macro defects on the substrates. 15,16) The effective thickness of an as-grown GaN boule is decreased by V-shaped pits, reducing the number of sliced wafers without penetrated pits (holes) and increasing the cost for GaN wafers. Reference 11 demonstrated that pits on c-GaN are composed of {1011} facets.…”
Section: Introductionmentioning
confidence: 99%